Interaksi Interpersonal Penggunaan Bahasa Kemayu antar Penari di Sanggar Makuta Gorontalo - Fazrin Bahtiar; Ridwan Ibrahim; Dewinta Rizky R. Hatu; Sabrina Nadia (Sosiologi Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Language serves as a fundamental instrument of communication that is essential in establishing and maintaining social relationships among individuals and groups. Beyond its role as a channel for transmitting information, language also operates as a marker of identity, a symbol of solidarity, and a medium for self-expression. In social development, different communities often develop specific linguistic variations that are exclusively used by their members. One example of such variation is the Kemayu language, which is employed by dancers at Makuta Dance Studio in Gorontalo as their everyday means of communication. The use of Kemayu language is an intriguing subject of study because it functions not only as a communicative tool but also carries social meanings that shape interpersonal relationships among group members. This research aims to explore the forms of interpersonal interaction that emerge through the use of Kemayu language among dancers at Makuta Dance Studio, Gorontalo. A qualitative research design with a descriptive approach was applied in this study. Data were gathered through observation, interviews, and documentation. The participants consisted of dancers who actively utilize Kemayu language in their daily interactions. The study employs George Herbert Mead’s Symbolic Interaction Theory to examine symbolic meanings, communication patterns, and social interaction processes among the dancers. The findings indicate that Kemayu language functions as a distinctive communicative system that symbolizes closeness, group identity, and privacy in conversations. Its usage is predominantly observed within the studio environment or during interactions among fellow dancers. Furthermore, Kemayu language reflects solidarity, emotional comfort, and expressive freedom among its users. The vocabulary is formed through modifications of both Indonesian and local languages. Overall, the use of Kemayu language demonstrates an ongoing process of symbolic exchange and shared social meaning that strengthens interpersonal relationships among dancers at Makuta Dance Studio in Gorontalo.